Numerical model of protein crystal growth in a diffusive field such as the microgravity environment. (1st October 2013) - Tanaka, Hiroaki; Sasaki, Susumu; Takahashi, Sachiko; Inaka, Koji; Wada, Yoshio; Yamada, Mitsugu; Ohta, Kazunori; Miyoshi, Hiroshi; Kobayashi, Tomoyuki; Kamigaichi, Shigeki
<x xml:space="preserve">Abstract</x> It is said that the microgravity environment positively affects the quality of protein crystal growth. The formation of a protein depletion zone and an impurity depletion zone due to the suppression of convection flow were thought to be the major reasons. In microgravity, the incorporation of molecules into a crystal largely depends on diffusive transport, so the incorporated molecules will be allocated in an orderly manner and the impurity uptake will be suppressed, resulting in highly ordered crystals. Previously, these effects were numerically studied in a steady state using a simplified model and it was determined that the combination of the diffusion coefficient of the protein molecule (D) and the kinetic constant for the protein molecule (β) could be used as an index of the extent of these depletion zones. In this report, numerical analysis of these depletion zones around a growing crystal in a non‐steady (i.e. transient) state is introduced, suggesting that this model may be used for the quantitative analysis of these depletion zones in the microgravity environment.